Postactivation Potentiation and Its Practical Applicability: A Brief Review - Robbins, Daniel W. (Journal of strength and conditioning research, 2005)
It has been suggested that postactivation potentiation (PAP) may be manipulated to enhance both acute performance and chronic adaptation. PAP refers to the phenomenon by which acute muscle force output is enhanced as a result of contractile history. Evidence exists regarding the existence of PAP. However, the determination of methods to best manipulate and exploit PAP remains elusive. Studies to date would seem to indicate that the practical applicability of PAP in terms of enhancing athletic performance is limited.